2000
DOI: 10.1177/230949900000800210
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Heterotopic Bone Formation in High Risk Patients Post-Total Hip Arthroplasty

Abstract: A retrospective study was carried out to evaluate prophylaxis for heterotopic ossification (HO) about the hip joint post total hip arthroplasty (THA). Between 1990 and 1996, 20 patients with known risk for developing HO were treated prophylactically to prevent this complication. Patients at risk were divided into 3 groups based on risk factors for HO formation (previous ipsilateral hip HO formation, previous contralateral hip HO formation and bilateral hypertrophic osteoarthritis) Single fraction radiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…With a brief literature review, we found studies taking an opposing view to this study in which additional medication to radiotherapy caused no improvement of the clinical outcome [1]. Combined treatments were used post actebular fractures and were found to be effective [4].…”
mentioning
confidence: 73%
“…With a brief literature review, we found studies taking an opposing view to this study in which additional medication to radiotherapy caused no improvement of the clinical outcome [1]. Combined treatments were used post actebular fractures and were found to be effective [4].…”
mentioning
confidence: 73%
“…Even with prophylactic radiotherapy a recurrence rate of over 50% has been reported. [27][28][29][30][31][32][33][34] In none of our five cases we found clinical or radiographic evidence for recurrence or new formation of HO following surgery. In addition, biochemical markers such as osteocalcin and alkaline phosphatase were within the normal range in all our patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, historical data on the natural outcome of excision surgery in this population of patients without treatment indicate a recurrence rate over 50%. [27][28][29][30][31][32][33][34] Accordingly, a recurrence of HO in at least two of our five patients would be anticipated. But in contrast, in none of our five high-risk patients such a recurrence occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically relevant ossifications develop in 20-45 % of all THA without prophylaxis compared to less than 5 % under an appropriate prophylaxis. Risk factors for HO include male gender, elderly, post-traumatic or hypertrophic osteoarthritis, rheumatoid arthritis, ankylosing spondylitis and Paget's disease [47][48][49][50]. Treatment of HO-related pain after THA is necessary when the patient experiences any If the nonoperative treatments fail then surgical resection of the ossification is the only therapeutic option [51].…”
Section: Bony Aspectsmentioning
confidence: 99%